2006
DOI: 10.1074/jbc.m510261200
|View full text |Cite
|
Sign up to set email alerts
|

SR-BI-mediated High Density Lipoprotein (HDL) Endocytosis Leads to HDL Resecretion Facilitating Cholesterol Efflux

Abstract: The high density lipoprotein (HDL) receptor, scavenger receptor class B, type I (SR-BI), mediates selective cholesteryl ester uptake from lipoproteins into liver and steroidogenic tissues but also cholesterol efflux from macrophages to HDL. Recently, we demonstrated the uptake of HDL particles in SR-BI overexpressing Chinese hamster ovarian cells (ldlA7-SRBI) using ultrasensitive microscopy. In this study we show that this uptake of entire HDL particles is followed by resecretion. After uptake, HDL is localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
102
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 64 publications
10
102
1
2
Order By: Relevance
“…Other studies suggest that transfection mediated SR-BI overexpression by COS cells can alter the lipid organization of cell membranes and that the proposed binding independent SR-BI-mediated efflux might be a consequence of lipid organization [293,294]. Pagler et al [295] suggest that retroendocytosis of HDL is mediated by SR-BI and that resecretion of HDL particle is accompanied by an efflux of cellular cholesterol.…”
Section: Scavenger Receptor Bi (Sr-bi)mentioning
confidence: 99%
“…Other studies suggest that transfection mediated SR-BI overexpression by COS cells can alter the lipid organization of cell membranes and that the proposed binding independent SR-BI-mediated efflux might be a consequence of lipid organization [293,294]. Pagler et al [295] suggest that retroendocytosis of HDL is mediated by SR-BI and that resecretion of HDL particle is accompanied by an efflux of cellular cholesterol.…”
Section: Scavenger Receptor Bi (Sr-bi)mentioning
confidence: 99%
“…20). Our earlier data demonstrate that HDL uptake and resecretion mediated by SR-BI provide an alternative form of cellular cholesterol efflux (2). Here, we hypothesize that cholesterol efflux mediated by HDL resecretion may be important in cells with disturbed cholesterol efflux, in which HDL might serve as the central cholesterol-distributing platform.…”
mentioning
confidence: 77%
“…Several mechanisms for cholesterol efflux have been described in detail, such as cell surface cholesterol efflux to nascent and mature HDL (1). Recently, we demonstrated that HDL retroendocytosis can be associated with cholesterol efflux (2). HDL uptake, visualized by single-dye tracing (3), and resecretion occurred in hepatocytes, macrophages, and adrenocortical cells (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations